Nanoremediation technologies for sustainable remediation of contaminated environments: recent advances and challenges - Ganie, Adil Shafi; Bano, Sayfa; Khan, Nishat; Sultana, Saima; Rehman, Zubair; Rahman, Mohammed M.; Sabir, Suhail; Coulon, Frederic; Khan, Mohammad Zain (Elsevier, 2021)
A major and growing concern within society is the lack of innovative and effective solutions to mitigate the challenge of environmental pollution. Uncontrolled release of pollutants into the environment as a result of urbanisation and industrialisation is a staggering problem of global concern. Although, the eco-toxicity of nanotechnology is still an issue of debate, however, nanoremediation is a promising emerging technology to tackle environmental contamination, especially dealing with recalcitrant contaminants. Nanoremediation represents an innovative approach for safe and sustainable remediation of persistent organic compounds such as pesticides, chlorinated solvents, brominated or halogenated chemicals, perfluoroalkyl and polyfluoroalkyl substances (PFAS), and heavy metals. This comprehensive review article provides a critical outlook on the recent advances and future perspectives of nanoremediation technologies such as photocatalysis, nano-sensing etc., applied for environmental decontamination. Moreover, sustainability assessment of nanoremediation technologies was taken into consideration for tackling legacy contamination with special focus on health and environmental impacts. The review further outlines the ecological implications of nanotechnology and provides consensus recommendations on the use of nanotechnology for a better present and sustainable future
Keywords: Nano-sensors; Photocatalysis; Persistent organic pollutants; Environmental sustainability; Nanoremediation